Characterization of municipal solid waste (MSW) - Paunovic, Perica; Hadzi-Jordanov, Svetomir (Macedonian Journal of Ecology and Environment, 2001)
Due to the enormous increase of Planet Earth’s population and intensive industrial activities, the superproduction of Municipal Solid Waste (MSW) is inevitable. Thus, the MSW is a global threat. Republic of Macedonia is not an exception. The exact identification of the local MSW quantity, composition and properties, as a starting point in each serious approach to the MSW-problem, is stressed out- in contrast to the existing habit to quote data for other communities. Methods for MSW quantity and composition estimation as well of its calorific value are listed. To achieve that goal an approach is suggested with as little as possible experimentation and corresponding use of acquisited knowledge and statistical treatment.